ANALISIS PRINSIP KESANTUNAN BERBAHASA DALAM PODCAST WARUNG KOPI PADA KANAL YOUTUBE HAS CREATIVE EDISI DESEMBER 2025 - Yuliana, Dela; Ahada Wahyusari; Isnaini Leo Shanty; Fabio Testy Ariance Loren; Abdul Malik; Dody Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of applying the principles of language politeness in communication, particularly in digital media such as podcasts, which feature spontaneous interactions. The objective of this study is to describe the forms of compliance with and violations of the principles of language politeness in the Warung Kopi podcast on the HAS Creative YouTube channel, December 2026 edition, based on Geoffrey Leech's Politeness Principle theory. This study employed a qualitative approach using a descriptive research design. The findings reveal that the Warung Kopi podcast contains utterances that both comply with and violate the six maxims of Leech's Politeness Principle, namely the Tact Maxim, Generosity Maxim, Approbation Maxim, Modesty Maxim, Agreement Maxim, and Sympathy Maxim. Compliance with the principles of language politeness is reflected in utterances that respect interlocutors, express appreciation, demonstrate empathy, and promote harmonious communication. In contrast, violations of the principles of language politeness are found in utterances containing direct criticism, explicit disagreement, disrespectful attitudes, and expressions that have the potential to offend the interlocutors. The findings indicate that language use in the podcast is influenced by the casual conversational context, the spontaneity of the speakers, and the close interpersonal relationships among the participants, resulting in both compliance with and violations of the principles of language politeness.